Spaces of longing and belonging: territoriality, ideology and creative identity in literature and film (Colloquia Comparativa Litterarum, 2025)
Spaces of Longing and Belonging: Territoriality, Ideology and Creative Identity in Literature and Film. Еds. Brigitte Le Juez and Bill Richardson, Brill Rodopi, 2019.